2018
DOI: 10.1038/s41374-018-0054-3
|View full text |Cite
|
Sign up to set email alerts
|

Spatially correlated phenotyping reveals K5-positive luminal progenitor cells and p63-K5/14-positive stem cell-like cells in human breast epithelium

Abstract: Understanding the mechanisms regulating human mammary epithelium requires knowledge of the cellular constituents of this tissue. Different and partially contradictory definitions and concepts describing the cellular hierarchy of mammary epithelium have been proposed, including our studies of keratins K5 and/or K14 as markers of progenitor cells. Furthermore, we and others have suggested that the p53 homolog p63 is a marker of human breast epithelial stem cells. In this investigation, we expand our previous stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
18
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 83 publications
(81 reference statements)
0
18
0
1
Order By: Relevance
“…Indeed, K5/K18 and K14/K18 double-positive cells are not uncommon in human TDLUs 61 . More recently, Boecker et al 65 identified K5 + K18/19 − and K5 + K18/K19 + populations in the luminal layer of ductal and TDLU breast tissue in situ 65 , while in human breast epithelial populations isolated by flow cytometry, the progenitor populations (Lin − CD49f + EpCAM hi ) include cells double-positive for K5/6 and K14 — and notably are also c-KIT + 40 . To add to the complexity of these marker patterns, K19 has been described both as a marker of progenitors 66 68 and highly expressed in differentiated luminal ER + cells 6 , 69 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, K5/K18 and K14/K18 double-positive cells are not uncommon in human TDLUs 61 . More recently, Boecker et al 65 identified K5 + K18/19 − and K5 + K18/K19 + populations in the luminal layer of ductal and TDLU breast tissue in situ 65 , while in human breast epithelial populations isolated by flow cytometry, the progenitor populations (Lin − CD49f + EpCAM hi ) include cells double-positive for K5/6 and K14 — and notably are also c-KIT + 40 . To add to the complexity of these marker patterns, K19 has been described both as a marker of progenitors 66 68 and highly expressed in differentiated luminal ER + cells 6 , 69 .…”
mentioning
confidence: 99%
“…Boecker et al 65 termed the populations they identified as progenitors and intermediary cells, respectively, but it is difficult to definitively assign such functions purely on the basis of marker expression, or indeed ex vivo assays. Of course, human breast tissue cannot be lineage-traced through transgene activation as one can in the mouse, but use of cytochrome C oxidase (CCO) mutations in the mitochondrial genome has proven feasible as an approach.…”
mentioning
confidence: 99%
“…The basal cell layer is able to regenerate the whole mammary gland epithelial tree ( Böcker et al., 2002 ; Boecker and Buerger, 2003 ; Van Keymeulen et al., 2011 ). Development of LE and ME cells occurs in a complex hierarchical manner from the basal progenitors that can differentiate into both epithelial cell types depending on numerous signaling pathways and hormonal stimuli ( Arendt and Kuperwasser, 2015 ; Böcker et al., 2002 ; Boecker and Buerger, 2003 ; Boecker et al., 2018 ; Van Keymeulen et al., 2011 ). This epithelial differentiation process can be followed as changes in cell-type specific protein expression patterns, including expression of distinct cytokeratin (CK) family members ( Böcker et al., 2002 ; Boecker and Buerger, 2003 ; Boecker et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Development of LE and ME cells occurs in a complex hierarchical manner from the basal progenitors that can differentiate into both epithelial cell types depending on numerous signaling pathways and hormonal stimuli ( Arendt and Kuperwasser, 2015 ; Böcker et al., 2002 ; Boecker and Buerger, 2003 ; Boecker et al., 2018 ; Van Keymeulen et al., 2011 ). This epithelial differentiation process can be followed as changes in cell-type specific protein expression patterns, including expression of distinct cytokeratin (CK) family members ( Böcker et al., 2002 ; Boecker and Buerger, 2003 ; Boecker et al., 2018 ). Less than 5% of the mammary basal cells represent mammary stem cells that express CK5 without luminal epithelial (LE) markers CK8/18/19 or myoepithelial (ME) marker α-SMA ( Böcker et al., 2002 ; Fu et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation